Polymorphisms of miR-196a2 (rs11614913) and miR-605 (rs2043556) confer susceptibility to gastric cancer - Poltronieri-Oliveira, Ayla Blanco [UNESP]; Madeira, Fernanda Fernandez [UNESP]; Nunes, Denis Bruno Santos Marques [UNESP]; Rodrigues, Gabriela Helena [UNESP]; Lopes, Beatriz Camargo [UNESP]; Manoel-Caetano, Fernanda S. [UNESP]; Biselli, Joice Matos [UNESP]; Silva, Ana Elizabete [UNESP] (Elsevier, 2017)
Background and purpose MicroRNAs (miRNAs) have been appointed as potential biomarkers for gastric cancer. Recent evidences suggest that single-nucleotide polymorphisms (SNPs) in miRNAs may change the miRNA biogenesis and influence cancer susceptibility. The aim of this study was to investigate the association of Mir-SNPs in miR-27a rs895819, miR-125a rs12976445, miR-196a2 rs11614913, miR-499 rs3746444, and miR-605 rs2043556 and their effect, alone and combined, on gastric cancer risk. Methods DNA samples obtained from 151 gastric cancer (GC) patients and 249 non-cancer subjects (control) were genotyped using the Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) technique or the TaqMan® SNP Genotyping Assay. Multiple logistic regression analysis was used to assess the associations between the miRNA polymorphisms and GC risk according to log-additive, dominant, and recessive models. Combined genotype analyses were also performed, using Fisher's exact test. Results The Mir-SNPs miR-27a rs895819, miR-125a rs12976445 and miR-499 rs3746444 were not associated with risk of GC. However, the miR-196a2 rs11614913 TT variant genotype was associated with a significantly increased risk for GC in the recessive model (OR = 2.88; 95% CI = 1.45–5.72; P = 0.002), and miR-605 rs2043556 AG and GG genotype carriers showed a significantly higher risk for GC in both the dominant (adjusted OR = 1.79; 95% CI = 1.14–2.82; P = 0.001) and the log-additive models (OR = 1.46; 95% CI = 1.01–2.12; P = 0.044). The combined genotype analysis showed that the presence of the three risk genotypes miR-27a G/miR-125a C/miR-605 G is associated with higher risk of GC (OR = 11.00; 95% CI = 1.13–106.5; P = 0.046). In addition, the combined genotype analysis of only miR-196a2 rs11614913 and miR-605 rs2043556 revealed that individuals carrying both risk alleles (miR-196a2 T/miR-605 G) also presented a significantly higher risk for GC compared to double wild-type homozygous individuals (OR = 2.00; 95% CI = 1.08–3.71; P = 0.031). Conclusions Our data showed that miR-196a2 rs11614913 and miR-605 rs2043556, alone or in combination, modulate the risk of developing GC in a Brazilian population, and that the combined genotypes miR-27a G/miR-125a C/miR-605 G may potentiate this risk.
Keywords: Cancer risk; Gastric cancer; Genotyping; MicroRNAs; Polymorphisms